ANALISIS DAN PERANCANGAN UI/UX PADA STARTUP RENOVACTION MENGGUNAKAN METODE USER CENTERED DESIGN - Muhammad Ariq Dzaky; Junaedy; Izmy Alwiah Musdar (STMIK KHARISMA Makassar, 2022)
This research aims to find out whether user centered design methods can have a good influence on an analysis and design of user interfaces and user experiences on a website. The author used the user centered design method approach, likert scale and merit webuse scale in this research to find out if the design results that have been worked have become the design needed by the user. The results that have been obtained from this research is getting the final value of likert scale and webuse calculations and the results is Very Agreeable and Excellent, and it can be concluded if the approach method by using user centered design methods in the analysis and design of user interface and user experience can provide excellent results and it can make it easier for users to useing the RenovAction website.